SELECTION OF PATIENTS WITH CONCOMITANT CHRONIC OBSTRUCTIVE DISEASE FOR ANATOMICAL RESECTIONS IN LUNG CANCER (review of literature) - A. L. Akopov; S. D. Gorbunkov; A. I. Romanikhin; M. G. Kovalev (Вестник хирургии имени И.И. Грекова)
The analysis of literature on the possibility of performing anatomical pulmonary resections in patients with concomitant COPD was performed. According to most researchers, FEV1 and DL (CO) more than 80 % indicated a high probability of an uncomplicated postoperative period after any anatomical resection of the lung. If the specified parameters were less than 80 %, additional studies were required: functional tests (6-minute walk test, staircase test), stress testing, calculation of predicted postoperative values of respiratory function, and, if necessary, lung scintigraphy could be performed to study regional respiratory function. The decision about the possibility and need for surgical treatment should have been made individually at the threshold values of these parameters. At the same time, there is currently no system for assessing the risk of postoperative complications for a particular patient, based on all the information about it, which represents the potential for further research.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.